Small bowel obstruction secondary to primary enterolith: A rare and delayed complication of radiation enteritis. Issue 3 (16th January 2021) - Seretis, Charalampos; Archer, Lucy; Elhassan, Mohammed Ali; Gurung, Deborah; Palit, Amitabh; Zayyan, Kassim
Abstract: Primary enteroliths as a result of pelvic radiotherapy are a rare cause of intestinal obstruction. Abstract : Primary enteroliths as a result of pelvic radiotherapy are a rare cause of intestinal obstruction